1999
DOI: 10.1007/s004420050916
|View full text |Cite
|
Sign up to set email alerts
|

Growth and protection against oxidative stress in young clones and mature spruce trees ( Picea abies L.) at high altitudes

Abstract: Clones of Norway spruce (Picea abies L.) were grown for several years on an altitudinal gradient (1750 m, 1150 m and 800 m above sea level) to study the effects of environmental × genetic interactions on growth and foliar metabolites (protein, pigments, antioxidants). Clones at the tree line showed 4.3-fold lower growth rates and contained 60% less chlorophyll (per gram of dry matter) than those at valley level. The extent of growth reduction was clone-dependent. The mortality of the clones was low and not alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…While many secondary products are clearly inducible—synthesized in response to environmental insult—in other cases plants have gradually adapted to harsh environments, and will routinely synthesize specific, protective phytochemicals even before encountering stress. The inherent high antioxidant phytochemical concentration in foliage of spruce trees, particularly in genotypes that have adapted to high elevations, is a striking example of genotype and environment interactions which influence the bioactive potential of the plant chemicals 24…”
Section: Nature/nurture Interactions and Phytochemical Accumulationmentioning
confidence: 99%
“…While many secondary products are clearly inducible—synthesized in response to environmental insult—in other cases plants have gradually adapted to harsh environments, and will routinely synthesize specific, protective phytochemicals even before encountering stress. The inherent high antioxidant phytochemical concentration in foliage of spruce trees, particularly in genotypes that have adapted to high elevations, is a striking example of genotype and environment interactions which influence the bioactive potential of the plant chemicals 24…”
Section: Nature/nurture Interactions and Phytochemical Accumulationmentioning
confidence: 99%
“…A large body of information on ozone effects is available for herbaceous plants (e.g., D'Haese et al, 2005;Herbinger et al, 2002;Burkey and Eason, 2002;Pasqualini et al, 2001) and tree seedlings (e.g., Padu et al, 2005;Tausz et al, 2004 b;Strohm et al, 2002;Matyssek and Innes, 1999), often based on dynamic or open-top chamber experiments. Studies on ozone effects with adult trees have mostly been conducted under natural ozone mixing ratios (e.g., Haberer et al, 2006;Calzada et al, 2001;Polle et al, 1999;Luwe, 1996). Information about the influence of long-term free-air ozone fumigation on adult trees is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Hausladen et al (1990) and Luwe (1996) found an accumulation of GSSG in 0 3-polluted spruce needles and a decrease in the GSH/GSSG ratio, respectively (Schmieden et al 1993). An accumu lation of dehydroascorbate in 0 3-polluted Spruce needles has never been detected (Ranieri et al 1999 because ozone cannot penetrate the plasma membrane (Polle et al, 1999) and reacts exclusively with cell wall bound ascor bic acid by the formation of dehydroascorbate, which is immediately transported into the cytosol and is regenerated by GSH. Since ascorbic acid is transported back again in the apoplast after its regeneration, no significant concentration changes between the reduced and oxidized form are found in either the apoplast or the symplast (Turcsänyi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%